Current situation of competitiveness and sustainability and COVID-19 (2020)
Thinking about what the future will be is not an easy task. The year 2020 has greatly marked the meaning of our lives, modifying all social, economic, and environmental dynamics. At the end of the last century, the United Nations (UN) in its publication "Our Common Future" (1987) warned of an over-exploitation of natural resources as economic growth became the primary objective of countries (Costanza et al., 2014). Likewise, the UN proposed working simultaneously and with the balance in the economic, human, environmental, institutional and technological dimensions to ensure sustainability, where the mixture of these gave way to competitiveness through the optimization of resources, as well as the forms and actions of social, economic and political agents to achieve adequate and sustained growth and development (Lombana & Rozas, 2009). Received: 26/11/2020. Accepted: 28/11/2020.  Published: 01/12/2020